Perancangan Enterprise Architecture Pada Bidang Perencanaan Dan Bidang Keuangan Di Pt. Pln Distribusi Jawa Barat Menggunakan Framework Togaf Adm - Mutia Dewi Kurniasih; Yuli Adam Prasetyo; Faishal Mufied Al Anshary (eProceedings of Engineering, 2016)
PT. PLN (Persero) Distribusi Jawa Barat (PLN DJB) as a State-Owned Enterprise which is mandated by the Law to provide sufficient electricity supply (availability) with adequate quality and reliability and at an affordable price (efficiency), PLN DJB need information systems that are supported by adequate technology infrastructure In addition, government policy related to accounting and IT governance for SOE became a challenge to align business strategy and IT strategy in accordance with the needs of PLN DJB. Enterprise architecture is one of methods that can be used to align business strategy and information technology strategy that is designed to suit the business needs. TOGAF ADM is one framework that can be used as a reference in building enterprise architecture. Phases used in this study only include six phases which preliminary phase until opportunities and solutions phase. The output of this research is business architecture blueprint, information systems architecture blueprint, and technology architecture blueprint. After obtaining a blueprint, then it can be made IT Development Roadmap at PLN DJB. Hopefully, with the design of the Enterprise Architecture (EA) on the Bidang Perencanaan dan Bidang Keuangan in PLN DJB can help companies to create competitive advantage through IT. Keywords: Enterprise Architecture, TOGAF ADM, Energy Company